Re-thinking the unimpeded tube-well growth under the depleting groundwater resources in the Punjab, Pakistan - Watto, Muhammad Arif; Mugera, Amin W.; Kingwell, Ross; Saqab, Muhammad Mudasar (Hydrogeology journal, 2018)
Groundwater resources are crucial in sustaining agro-ecosystems and ensuring food security in many parts of the world, including Pakistan. However, the sustainability of groundwater resources is subject to a number of challenges, including over-extraction, deterioration in quality, and vulnerability to the impacts of climate change and population growth. Given the current state of groundwater resources in Pakistan, policymakers seek to manage groundwater resources by limiting groundwater extraction. To achieve this goal on a national scale, it is important to understand the determinants of the decisions made by local farmers in respect of tube-well adoption. This study investigates smallholder farmers’ decisions to adopt tube-well technology in the face of dwindling groundwater resources and falling water tables. Analysis is based on a cross-sectional survey of 200 rural households from the arid to semi-arid predominantly groundwater-irrigated plains of the Punjab province, Pakistan. It is found that farmers will adopt tube-well technology in pursuit of reliable irrigation water supplies to hedge against production risks but not against the risk associated with unfavourable extreme events (downside risk) such as total crop failure. This suggests that the adoption decision is influenced by the expected long-term rather than the short-term benefits. This paper draws attention to the need to regulate groundwater resource exploitation by requiring the use of tube-well technology to be accompanied by irrigation water-efficient techniques and technologies.